The effects of core training on endurance in different trunk movements: A systematic review and meta-analysis - Barrio, E. D.; Hernandez-García, R.; Ramírez-Campillo, R.; de Alcaraz, A. G. (Kinesiology, 2024)
Core muscle endurance involves the trunk muscles` capability to maintain a particular position for as much time as possible. It is essential to know how specific training aimed at this area affects endurance of different trunk movements performance and to what extent. The objective was to assess the effects of trunk training on different core muscle endurance measurements in flexion, extension, and right and left lateral flexion. A literature search was performed using different databases. The studies included: (a) cohorts of healthy people or subjects with chronic low back pain; (b) a core training intervention; (c) pre-post intervention parameters of interest; (d) a minimum of four out of 10 on the PEDro scale, and (e) randomised controlled trials. A random-effects model for meta-analyses was used. Fifteen studies were selected for the systematic review and 11 for the meta-analysis, comprising 1,213 participants. Compared to the control condition, core training induced a moderate effect on trunk flexion endurance (ES = 0.67), right-lateral trunk flexion endurance (ES = 0.77), left-lateral trunk flexion endurance (ES = 0.94), and a small effect on trunk extension endurance (ES = 0.49). To back up the results presented in this study, more research into the effects of trunk training on core muscle endurance is needed to confirm these results significantly. Core training improves core muscle endurance in four trunk movements. Core training is more effective in participants with pre-intervention poor results.